(untitled) (Fiep Bulletin - online, 2014)
The process of formation of intern is done by the internship practice, because it is the way to do the transition from the university student to the professor. This article presents a pilot study that aims to survey the student’s expectations about the coherence between the Supervised Internship and the labor market. A questionnaire with 5 questions was applied to the 32 senior university interns from Physical Education Course of Universidade Presidente Antônio Carlos - UNIPAC Ipatinga as the instrument. It involved 5 aspects such as: a) perception about the internship; b) expectations in relation to the labor market before the internship; c) impact in the Supervised Internship practice as for the labor market reality; expectations in relation to work market after the supervised internship; e) the effectiveness of the internship to the labor market. The results show that the internship has the function to insert the individuals in the labor market for each teaching. Other important point is about the differences that concern to the reality of educational practice at the public and private schools. In a general way, it was possible to assimilate that supervised internship carries out its function although it is necessary to the intern look for continuous improvement.